1992
DOI: 10.1172/jci115558
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipolysis and its consequences on gluconeogenesis in non-insulin-dependent diabetes mellitus.

Abstract: The present studies were undertaken to determine whether Iipolysis was increased in non-insulin-dependent diabetes mellitus (NIDDM) and, if so, to assess the influence of increased glycerol availability on its conversion to glucose and its contribution to the increased gluconeogenesis found in this condition. For this purpose, we infused nine subjects with NIDDM and 16 age-, weight-matched nondiabetic volunteers with 12-3H1 glucose and IU-'4C1 glycerol and measured their rates of glucose and glycerol appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
0
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(134 citation statements)
references
References 32 publications
9
123
0
2
Order By: Relevance
“…For the NZO mice which had a wide range of glycerol concentrations, there was a positive correlation (r --0.81, p < 0.05) between the two parameters. As has been shown in human NIDDM [19], for the same glycerol concentrations, NZO mice converted more of this substrate to glucose than the control mice. This suggests an increase in the intrahepatic conversion of glycerol to glucose in the obese animals.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…For the NZO mice which had a wide range of glycerol concentrations, there was a positive correlation (r --0.81, p < 0.05) between the two parameters. As has been shown in human NIDDM [19], for the same glycerol concentrations, NZO mice converted more of this substrate to glucose than the control mice. This suggests an increase in the intrahepatic conversion of glycerol to glucose in the obese animals.…”
Section: Resultssupporting
confidence: 69%
“…Previous studies have shown that in NIDDM elevated NEFA levels are at least partly responsible for impaired suppression of HGP by insulin [14,42,43]. Furthermore, as with the NZO mouse, NIDDM patients have increased conversion of glycerol to glucose [19,20]. Nurjhan et al [19] infused glycerol into control patients to match the levels seen in obese diabetic patients, and found that the control patients still had lower rates of glycerol conversion to glucose than the NIDDM patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations